Adjusting to sex and intimacy: Gynecological cancer survivors share about their partner relationships. (3rd May 2020) - Abbott-Anderson, Kristen; Young, Patricia K.; Eggenberger, Sandra K.
ABSTRACT: This study describes what gynecological (GYN) cancer survivors relate about their intimate partners and adjustments in their sexual lives following diagnosis and treatment. Conventional descriptive content analysis was used to examine participant responses about partner relationships following their diagnosis. Responses revealed three clusters and 15 codes of data. Findings report the influence of cancer treatment on sexual activity and functioning, women's sex lives, and their relationships. Health-care providers have a vital role in supporting women and their partners during the cancer care trajectory and should include both the survivor and the partner in conversations focused on sexual concerns and sexual well-being.